1996
DOI: 10.1111/j.1365-2842.1996.tb00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Human mastication modulated by experimental trigeminal and extra‐trigeminal painful stimuli

Abstract: This paper describes the modulation of human deliberately unilateral mastication by trigeminal and extra-trigeminal standardized painful stimuli. Series with 15 s of gum-chewing before induction of pain, during pain and after pain were quantitatively assessed by jaw-closing muscle electromyography (EMG) and kinematics of the lower jaw. Four different painful stimuli were used: cold stimulation of the frontal region, cold stimulation of the dominant hand, capsaicin stimulation of the hard palate, and pressure p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is well known that acute orofacial pain can modulate orofacial motor behaviour. For example, in humans, intra‐oral pain has been shown to modulate the EMG activity associated with the jaw‐closing muscles (28) and more recently, noxious stimulation with glutamate to the rat tongue, but not the masseter muscle, can modulate licking behaviour (29). Previously, our group has also shown that rapid changes in cortical excitability of the tongue MI, as measured by TMS, and the gains in motor performance that would otherwise occur in association with novel tongue‐task training were inhibited by capsaicin‐induced tongue pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that acute orofacial pain can modulate orofacial motor behaviour. For example, in humans, intra‐oral pain has been shown to modulate the EMG activity associated with the jaw‐closing muscles (28) and more recently, noxious stimulation with glutamate to the rat tongue, but not the masseter muscle, can modulate licking behaviour (29). Previously, our group has also shown that rapid changes in cortical excitability of the tongue MI, as measured by TMS, and the gains in motor performance that would otherwise occur in association with novel tongue‐task training were inhibited by capsaicin‐induced tongue pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…Before the adjustment of the occlusal splint, the digital evaluation revealed that in the maximum intercuspal position the force of distribution was %40.8 for the right activity in the pain side and the increased EMG activity of the temporalis anterior muscle in the non-pain-side that could be related to the "pain adaptation model." Previously, it has been shown in several clinical studies and in experimental muscle pain studies 13 that a decrease of the EMG activity in the painful muscle and an increase in the EMG activity in nonpainful muscles was found during the dynamic contractions. 14 Lund et al 15 have described the interaction between the muscle pain and muscle coordination with the "pain-adaptation model" that lead to the increased activity of antagonistic muscle and the decreased activity of agonistic muscle during muscle pain.…”
Section: Discussionmentioning
confidence: 97%